Evaluation of different fragment sizes and cryoprotectants for cryopreservation of feline testicular tissues - Macente, B. I. [UNESP]; Toniollo, G. H. [UNESP]; Apparicio, M.; Mansano, C. F.M. [UNESP]; Thomé, H. E.; Canella, C. L.; Tozato, M. E.G. [UNESP]; Gutierrez, R. R. [UNESP] (Wiley, 2017)
This study aimed to evaluate tissue damage of feline testicles sectioned in two different sizes (0.3 or 0.5 cm3) and submitted to different cryoprotectants (propanediol or glycerol). Testicles obtained from 12 domestic cats were sectioned in 0.3 and 0.5 cm3 sized pieces and immediately evaluated by TBARS and semi-quantitatively by histomorphology. The remaining fragments were placed in cryotubes with 1 ml Egg yolk Tris Equex STM extender containing 3% glycerol or 3% propanediol and cryopreserved by fast-freezing technique. Frozen-thawed fragments were also evaluated by TBARS and histomorphology. Statistical analysis was performed using one-way ANOVA with Student–Newmann–Keuls post hoc test, with p <.05. Fresh and cryopreserved tissues generally exhibited a similar morphology concerning detachment of cells from the basement membrane and observation of nucleoli, with a great proportion scored as 0 (no alteration). When present, alterations were slight and the morphology was considered to be good (most classified in scores 1). Pyknosis was the main anomaly observed as score 2 in 54.6% and 58.4% of 0.3-cm3 fragments cryopreserved in propanediol and glycerol, respectively (16.7% scored 2 in fresh tissue). In TBARS evaluation, 0.5-cm3 fragments cryopreserved in glycerol produced less free radical compared to the 0.3 cm3 cryopreserved in glycerol or propanediol. Our results showed that glycerol was more efficient than propanediol to cryopreserve 0.5-cm3 fragments; this might be attributed to the fact that glycerol molecular weight is larger than propanediol and so its perfusion in the testicular tissue is slower.